Satellite NOAA 12 IR, sfc temps,winds, 500mb heights (GIF). Version 1.0 - Wiley, D. (UCAR/NCAR - Earth Observing Laboratory, 2007)
This data set contains NOAA 12 IR satellite pass at 0000 UTC daily. Overlay of surface winds and temperature analysis and 500mb heights for the SHEBA domain from SSEC at U. of Wisconsin are included.
Keywords: climatologyMeteorologyAtmosphere; Models/Analyses; Arctic; Satellite; Meteorology; POES NOAA-12; Earth Observation Satellites > NOAA POES (Polar Orbiting Environmental Satellites) > NOAA-12 > National Oceanic & Atmospheric Administration-12 > 6b3f1f0f-353b-45b7-9dc0-567afa2c82c5; Advanced Very High Resolution Radiometer - AVHRR; Earth Remote Sensing Instruments > Passive Remote Sensing > Spectrometers/Radiometers > Imaging Spectrometers/Radiometers > AVHRR > Advanced Very High Resolution Radiometer > e64e83bd-02b3-4a47-830d-00e1aa4b04d3; EARTH SCIENCE > ATMOSPHERE > ATMOSPHERIC TEMPERATURE > SURFACE TEMPERATURE > AIR TEMPERATURE; EARTH SCIENCE > SPECTRAL/ENGINEERING > INFRARED WAVELENGTHS > INFRARED IMAGERY; EARTH SCIENCE > ATMOSPHERE > ALTITUDE > GEOPOTENTIAL HEIGHT; EARTH SCIENCE > ATMOSPHERE > ATMOSPHERIC PRESSURE > SEA LEVEL PRESSURE; Arctic Ocean; SHEBA; Surface Heat Budget of the Arctic Ocean Project; S - U > SHEBA > Surface Heat Budget of the Arctic Ocean > af6c4ef7-c65e-4adb-a075-0ea9144dea95